THE HABITUATION OF CATUR PARAMITHA VALUES AS A PRACTICE OF CULTURAL COMMUNICATION AT SD LENTERA HATI - I Komang Ramadi Putra, (JKKB: Jurnal Kajian Komunikasi Budaya (JCCS: Journal of Cultural Communication Studies), 2025)
Character formation in elementary school children occurs not merely through the transfer of knowledge, but through the habituation of values embedded in daily interactions. This study analyzes the habituation of Catur Paramitha values as a form of cultural communication practice at SD Lentera Hati Jimbaran. The values of maitri (loving-kindness), karuna (compassion), mudita (empathetic joy), and upeksa (inner balance) are practiced through a series of daily and weekly programs such as morning activities, religious sessions, cooking classes, animal care activities, gardening, religious celebrations, and guidance and counseling programs. Adopting a qualitative approach within Spradley’s ethnographic tradition, data were collected through participant observation, in-depth interviews, and documentation. The findings reveal that value habituation occurs through processes of symbolic communication, exemplary behavior, and collective participation that foster empathy, mutual respect, and harmonious social relations among students of diverse religious and cultural backgrounds. The challenges identified include inconsistent family parenting patterns, limited supporting facilities, and the penetration of digital culture, which introduces linguistic and behavioral patterns that often contradict the Catur Paramitha values. The study underscores the role of schools as cultural spaces that produce and negotiate values, emphasizing that character value habituation should be cultivated through reflective, collaborative, and continuous processes.